2008
DOI: 10.1038/ncpendmet0844
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of male infertility secondary to morbid obesity

Abstract: SUMMARYBackground-A 29-year-old man presented to a clinic with infertility and hypogonadism in the setting of morbid obesity. On presentation, he had notable gynecomastia and a low testicular volume. The patient's weight was 154 kg and his height was 168 cm (BMI 54.5 kg/m 2 ). Before referral to the clinic, the patient had been treated with testosterone therapy for 4 months for hypogonadism. This treatment had caused his initially low sperm concentration to fall to undetectable levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 15 publications
(1 reference statement)
2
51
0
11
Order By: Relevance
“…Indeed, increased aromatisation of androgens steroids to oestrogens in adipose tissue in obese men were described a few decades ago; increased oestrogen levels are known to induce hypogonadotropic hypogonadism with the end result of decreasing total and free testosterone (Schneider et al 1979). Anecdotally, treatment of an obese patient with the aromatase inhibitor anastrozole, led to decreased serum oestradiol levels, normalising luteinising hormone (LH) and testosterone levels, and restored spermatogenesis and fertility (Roth et al 2008). This observation supports the therapeutic potential of aromatase in infertile obese men, though the use of these drugs for this aim in clinical practice needs to be supported by further evidence that can also grant future label recommendation.…”
Section: Energy Balance Hormonal Dysfunction and Male Reproductionmentioning
confidence: 75%
“…Indeed, increased aromatisation of androgens steroids to oestrogens in adipose tissue in obese men were described a few decades ago; increased oestrogen levels are known to induce hypogonadotropic hypogonadism with the end result of decreasing total and free testosterone (Schneider et al 1979). Anecdotally, treatment of an obese patient with the aromatase inhibitor anastrozole, led to decreased serum oestradiol levels, normalising luteinising hormone (LH) and testosterone levels, and restored spermatogenesis and fertility (Roth et al 2008). This observation supports the therapeutic potential of aromatase in infertile obese men, though the use of these drugs for this aim in clinical practice needs to be supported by further evidence that can also grant future label recommendation.…”
Section: Energy Balance Hormonal Dysfunction and Male Reproductionmentioning
confidence: 75%
“…In fact, no malformed babies were fathered by infertile males in the course of this treatment. 4,12,13 Additional studies have also shown that letrozole does not increase the risk for congenital malformations with ovulation induction. 14 If our data are confirmed, this and future research may save some NOA patients from surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, aromatase inhibitors are believed to increase sperm count, androgen and gonadotropin levels and to lower blood E2 levels in oligoasthenoteratospermia patients. 12,13 Letrozole for non-obstructive azoospermia G Cavallini et al 896…”
Section: Discussionmentioning
confidence: 99%
“…86 This dysregulation is explained by the increased activity of aromatase cytochrome P450 enzyme, which is highly expressed in white adipose tissue. 85,87 This enzyme plays a key role in the biosynthesis of estrogen, and obese males have a high rate of conversion of androgens into estrogen due to a high bioavailability of aromatase enzymes. 87 Animal models have shown that high estrogen levels have a direct deleterious impact on spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…85,87 This enzyme plays a key role in the biosynthesis of estrogen, and obese males have a high rate of conversion of androgens into estrogen due to a high bioavailability of aromatase enzymes. 87 Animal models have shown that high estrogen levels have a direct deleterious impact on spermatogenesis. 88 Moreover, estrogen negatively regulates the secretion of gonadotropin-releasing hormone, luteinizing hormone, and follicle-stimulating hormone by the anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 99%